MODEL INOVATIF PERENCANAAN STRATEGIK BERBASIS PROGRAM 7 POE ATIKAN DALAM MENINGKATKAN PENDIDIKAN KARAKTER SISWA DI SDN TARINGGULLANDEUH - Gumelar, Dede Ipan; Mustopa, Epi Saepul; Haryati, Elis; Cahyono, Rendra Bagus; Handayani, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore and analyze the implementation of an innovative strategic planning model based on the 7 Poé Atikan program to strengthen character education at SDN Taringgullandeuh, Purwakarta. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that the strategic planning process has been partially applied through thematic character education integrated into daily school routines. However, formal documentation such as strategic plans and performance indicators remains limited. The organization of the program is relatively effective, with role distribution aligned to teacher competencies, though it lacks formal standard operating procedures. The implementation is consistent and culturally embedded, although constrained by resources and varying understanding of character themes among teachers. Evaluation remains informal and lacks standardized instruments, while follow-up actions rely on verbal coordination and are yet to be institutionalized. The study concludes that while the 7 Poé Atikan-based planning model is culturally relevant and effective in shaping student character, it requires reinforcement in documentation, evaluation systems, and strategic sustainability mechanisms. Keywords: Strategic Planning, Character Education, 7 Poé Atikan, Local Wisdom, Elementary Education